2020
DOI: 10.1002/jbt.22635
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation effect of polydeoxyribonucleotide on inflammatory cytokines and apoptotic factors induced by particulate matter (PM10) damage in human bronchial cells

Abstract: Particulate matter (PM) of 10‐μm‐sized fine dust in the air penetrates the respiratory tract and contributes to the increasing incidence of various lung diseases, but its definite mechanism is not known. Recently, polydeoxyribonucleotide (PDRN) has been shown to have anti‐inflammatory and regenerative effects in various tissues. However, the bronchial‐related mechanism is not well‐understood. Hence, this experiment is intended to demonstrate the beneficial effect of PDRN administration on PM10‐induced injury i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
(48 reference statements)
0
9
0
3
Order By: Relevance
“…Nanoparticles can retain for a long period of time in the atmosphere and easily move in the air. Chronic exposures of CFA can cause accumulation of sediments in the lungs and lead to serious adverse effects, such as inflammation in the alveolar cells [ 3 , 4 ]. Moreover, nanoparticles are responsible for many respiratory diseases, such as asthma, bronchitis, chronic obstructive pulmonary diseases (COPD), and lung carcinoma [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles can retain for a long period of time in the atmosphere and easily move in the air. Chronic exposures of CFA can cause accumulation of sediments in the lungs and lead to serious adverse effects, such as inflammation in the alveolar cells [ 3 , 4 ]. Moreover, nanoparticles are responsible for many respiratory diseases, such as asthma, bronchitis, chronic obstructive pulmonary diseases (COPD), and lung carcinoma [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…One study revealed that Ok-PDRN has anti-apoptotic and anti-inflammatory effects in human bronchial cells stimulated with 10-μm-sized particulate matter (PM) (fine dust) [ 16 ]. Ok-PDRN (0–8 μg/mL) ameliorated PM10-induced apoptosis without cytotoxicity on human bronchial cells and suppressed the production of inflammatory cytokines [interleukin (IL)-1β, IL-6, and tumor necrosis factor-α (TNF-α)] and apoptotic factors (caspase-3 and -9).…”
Section: Resultsmentioning
confidence: 99%
“…Activation of PKA enhanced phosphorylation of CREB, which led to the nuclear localization and activation of CREB [30]. Phosphorylation of CREB exerted anti-inflammatory effect [10,11] and improved short-term memory [31]. In the cur-rent study, PM-exposed trachea showed PKA phosphorylation was not changed and CREP phosphorylation was decreased, however PDRN treatment increased phosphorylation of PKA and CREB in PM-exposed mice.…”
Section: Discussionmentioning
confidence: 97%
“…It is well known that PM aspiration increases inflammatory factors and accelerates apoptotic cell death [2][3][4]6]. Reduced cell viability and production of TNF-α, IL-1β, and IL-6 were observed after exposure to PM10 in human bronchial-derived NCI-H358 cells [11]. Since the PM composition in the air has a high content of heavy metals and transition metals, its toxicity may cause damage to the human body [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation